Peranan Perbankan Syariah Terhadap Pengembangan Modal Usaha Mikro, Kecil dan Menengah (UMKM) - Ayif fathurrahman; Jihan Fadilla (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
This study aims to analyze the role of Islamic banking toward the development of Micro, Small and Medium Enterprises (MSMEs) capital in Yogyakarta. This test uses primary data obtained from the distribution of questionnaires with analysis tools using SPSS 20 software. The sampling method in this study used purposive sampling where 100 samples were selected according to the research criteria. In this study using the sample criteria with microfinance customers in Islamic banking in Yogyakarta. The data analysis technique in this test is multiple regression analysis. So, the results obtained in this test show that the variables of assistance, accessibility, and financing products have a positive and significant effect on capital development. However, the service variable does not have a positive and significant effect on MSMEs’ capital development in Yogyakarta.